2010
DOI: 10.1071/ch10331
|View full text |Cite
|
Sign up to set email alerts
|

Competition Between Azido Cleavage and Triplet Nitrene Formation in Azidomethylacetophenones

Abstract: Photolysis of p- and m-azidomethylacetophenone (1a, 1b) in argon-saturated solutions yields predominantly imine 2a, 2b, whereas irradiation of 1a, 1b in oxygen-saturated solutions results in heterocycles 3a, 3b, aldehydes 4a, 4b and nitriles 5a, 5b. Density functional theory calculations place the energy of the first and second excited state of the triplet ketones (T1K and T2K) in 1a, 1b in close proximity to each other. The triplet transition state for cleaving the C–N bond in 1a, 1b to form azido and benzyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
4
8
0
Order By: Relevance
“…However, we have previously shown that DFT calculations underestimate the energy of triplet ketones with (n,π*) configuration. 44,45 The calculated rotational barrier between the phenyl and ketone group for the T 1K of ester 1 is similar to the rotational barrier in the S 0 , or 6 kcal mol −1 (Fig. 5).…”
Section: Calculationssupporting
confidence: 62%
“…However, we have previously shown that DFT calculations underestimate the energy of triplet ketones with (n,π*) configuration. 44,45 The calculated rotational barrier between the phenyl and ketone group for the T 1K of ester 1 is similar to the rotational barrier in the S 0 , or 6 kcal mol −1 (Fig. 5).…”
Section: Calculationssupporting
confidence: 62%
“…Method as for 14a using compound 10 (320 mg, 0.95 mmol), 3-acetylbenzyl bromide [31] (59 wt%, 0.82 g, 2.25 mmol) and TEA (2.0 mL, 14.4 mmol) in ethanol (30 mL) at 120 °C for 30 h. Flash column chromatography (hexane/EtOAc 8:1 to 6:1) afforded compound 14q as a yellow oil (290 mg, 65%). 1 H NMR (270 MHz, CDCl 3 ): δ = 1.05 (18H, d, J = 6.7 Hz), 1.12-1.30 (3H, m), 2.60 (3H, s), 2.65-2.76 (4H, m), 3.54 (2H, s), 3.70 (5H, s), 6.42 (1H, s), 6.58 (1H, s), 7.42 (1H, t, J = 7.7 Hz), 7.62 (1H, dt, J = 7.7, 1.5 Hz), 7.86 (1H, dt, J = 7.7, 1.5 Hz), 7.95 (1H, t, J = 1.5 Hz).…”
Section: Methodsmentioning
confidence: 99%
“…However, triplet alkyl nitrenes can be formed by intermolecular and intramolecular sensitization of alkyl azides with acetophenone derivatives. [5][6][7][8][9][10] Acetophenone derivatives are excellent triplet sensitizers for alkyl azides because they absorb light at longer wavelengths than alkyl azides. In addition, acetophenone derivatives undergo intersystem crossing to their triplet states efficiently, with rate constants on the order of 10 11 s -1 and with quantum yields approaching unity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, intersystem crossing, either from the singlet excited state of the alkyl azide to its triplet excited state or from the singlet nitrene to its triplet configuration, must be slower than the formation of the imine product. However, triplet alkyl nitrenes can be formed by intermolecular and intramolecular sensitization of alkyl azides with acetophenone derivatives . Acetophenone derivatives are excellent triplet sensitizers for alkyl azides because they absorb light at longer wavelengths than alkyl azides.…”
Section: Introductionmentioning
confidence: 99%